A method to account for the effect of hydrodynamics on polar organic compound uptake by passive samplers. (30th January 2017) - Booij, Kees; Maarsen, Natasja L.; Theeuwen, Matthijs; van Bommel, Ronald
Abstract: Mass transfer coefficients of the water boundary layer ( k w ) were measured using alabaster dissolution kinetics in a diffusion cell that was operated at stirring rates between 90 min −1 and 600 min −1, aiming to provide a more robust characterization of the effect of hydrodynamics on the uptake of polar compounds by passive samplers, as compared with characterizations in terms of stirring rates and water flow velocities. The measured k w helped to quantitatively understand calcium sulfate transport through a poly(ethersulfone) membrane and 2 water boundary layers (at both sides of the membrane). Alabaster‐based k w value were used to understand atrazine transport in the diffusion cell, allowing the conclusion that atrazine transport in the membrane is via the pore space, rather than via the polymer matrix. The merits of measuring alabaster dissolution rates for passive sampler calibration and application in the field are discussed. The authors propose that passive sampler calibrations be carried out under controlled k w conditions, rather than under controlled stirring rates or flow velocities. This would facilitate the interpretation of passive sampler calibration studies and the translation of laboratory‐based water sampling rates to flow conditions that apply in the field. Environ Toxicol Chem 2017;36:1517–1524. © 2016 SETAC